An autocode programme to determine the flatness of a surface table using the least square mean plane criteria - Scarr, A. J. (College of Aeronautics, 1964)
Introduction The calculations involved in determining the flatness of a surface table from measurements made with instruments such as a block level or auto collimator can be lengthy, particularly where a large number of ordinates are taken. A solution to this problem is presented in this note in the form of an Autocode programme which will cater for up to 100 ordinates. The datum from which the variations in the flatness of the surface table are determined is the least squares mean plane. This may be defined as being that plane which makes the sum of the squares of the errors relative to it a minimum … [cont.].